2010
DOI: 10.1111/j.1475-4983.2010.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Azendohsaurus (Diapsida: Archosauromorpha) from the Triassic Isalo Group of southwestern Madagascar: cranium and mandible

Abstract: Here, we describe a new species of Azendohsaurus from the Middle-Late Triassic of Madagascar, extending the geographical range of a taxon known otherwise only by a single species from Morocco. Although Azendohsaurus has consistently been regarded as an early dinosaur (based on various advanced dental and gnathic features resembling those characterizing certain dinosaur subgroups), the relatively complete skeletal material, now available from Madagascar, argues strongly against its dinosaurian affinities. Rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
223
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(232 citation statements)
references
References 29 publications
9
223
0
Order By: Relevance
“…Additional material and a careful reevaluation of the specimens demonstrate that the purported 'sauropodomorph' material belongs to a taxon only distantly related to dinosaurs that shares uncanny modifications of the skull with plant-eating, large-bodied dinosaurs (Flynn et al, 2008;Flynn et al, 2010). Similarly, Nesbitt et al (2007) demonstrated that several supposed dinosaurs from the Late Triassic of North America actually represent dinosauromorphs, the closest relatives to dinosaurs rather than bona fide members of the group.…”
Section: Taxa Often Mistaken As Dinosaursmentioning
confidence: 99%
“…Additional material and a careful reevaluation of the specimens demonstrate that the purported 'sauropodomorph' material belongs to a taxon only distantly related to dinosaurs that shares uncanny modifications of the skull with plant-eating, large-bodied dinosaurs (Flynn et al, 2008;Flynn et al, 2010). Similarly, Nesbitt et al (2007) demonstrated that several supposed dinosaurs from the Late Triassic of North America actually represent dinosauromorphs, the closest relatives to dinosaurs rather than bona fide members of the group.…”
Section: Taxa Often Mistaken As Dinosaursmentioning
confidence: 99%
“…While some 43 authors have suggested that ornithischians were present in the Late Triassic of North America 44 (Heckert 2005) virtually all authors are in agreement that Crosbysaurus cannot be diagnosed 1 beyond an indeterminate archosauriform and new data suggest that it may be instead an non-2 archosauriform archosauromorph based on similar dental features found in the 3 archosauromorph Azendohsaurus (Flynn et al, 2010 Description -MNA V10666 (Fig. 5-7) is a single, nearly complete shed tooth crown.…”
Section: Introduction 26 27mentioning
confidence: 63%
“…This great diversification in morphological disparity by the Middle Triassic is perhaps not unexpected given the rapid, almost simultaneous diversification of archosauriforms (Brusatte et al, 2011;Butler et al, 2011; We have previously noted the convergent similarities of skull morphology and form of the marginal teeth between A. madagaskarensis and early sauropodomorph dinosaurs , many of which have been interpreted as herbivorous adaptations in early sauropodomorphs (Weishampel and Norman, 1989;Barrett, 2000;Sues, 2000;Goswami et al, 2005). For example, both A. madagaskarensis and early sauropodomorphs share convergences in marginal tooth crown structure and hemimandible architecture (see Flynn et al, 2010). As highlighted in the descriptions above, however, homoplasious similarities between A. madagaskarensis and early sauropodomorphs extend beyond craniodental features, occurring throughout much of the skeleton.…”
Section: Implications For the Divergencementioning
confidence: 99%
“…Azendohsaurus Dutuit, 1972 Azendohsaurus madagaskarensis Flynn et al, 2010 HOLOTYPE: (field number 7-20-99-653 Kammerer et al, 2010), rhynchosaurs (Isalorhynchus genovefae Buffetaut, 1983, Whatley, 2005, a kannemeyeriifrom dicynodont , an enigmatic archosaur (Nesbitt et al, unpublished data) and dinosauromorphs (Kammerer et al, unpublished data) occur in the Makay Formation within a 10 km radius of the Azendohsaurus producing locality. The stratigraphic relationships among these localities are not well Fig.…”
Section: Azendohsauridae (New)mentioning
confidence: 99%
See 1 more Smart Citation